Real-life effectiveness of transitioning from paliperidone palmitate 1-monthly to paliperidone palmitate 3-monthly long-acting injectable formulation - Olivier Corbeil; Anne-Marie Essiambre; Laurent Béchard; Audrey-Anne Roy; Maxime Huot-Lavoie; Sébastien Brodeur; Ranjith Chandrasena; Chantale Thériault; Candice Crocker; Jean-Pierre Melun; Phil Tibbo; Marie-France Demers; et al. (SAGE Publishing, 2022)
Background: Non-adherence to antipsychotics in schizophrenia is associated with an increased risk of psychotic relapse and hospitalization, a risk that is reduced with the use of long-acting injectable (LAI) antipsychotics. Randomized clinical trials (RCTs) have demonstrated the efficacy of paliperidone palmitate 3-monthly (PP3M) for psychotic relapse prevention in schizophrenia, but it remains poorly documented among individuals treated in real-life settings who can benefit the most out of LAIs. Objectives: The objective of this study was to evaluate the effectiveness of PP3M in relapse prevention among patients with schizophrenia. Methods: This is a multicentre retrospective study conducted in four outpatients' clinics across Canada. All consecutive patients with a main diagnosis of schizophrenia who initiated PP3M between June 2016 and March 2020 were included. The primary outcome was psychotic relapse, defined using broad and clinically relevant criteria. Results: Among 178 consecutive patients who were switched to PP3M, the 12-month relapse rate was 18.5% and the relapse-free survival probability was 0.788 (95% confidence interval [CI] = 0.725-0.856). Comorbid diagnoses of personality disorders and substance use disorders were associated with hazard rates (HRs) of 3.6 (95% CI = 1.8-7.3, p  < 0.001) and 3.1 (95% CI = 1.6-6.2), respectively. Increased psychopathology severity was associated with an increased likelihood of relapse, while having a job or being in school was protective. Conclusion: These findings reinforce the necessity of conducting research in patients with comorbid psychiatric disorders who are typically underrepresented in RCTs, yet overrepresented in real-life settings, in order to better inform and guide clinical practice.